Cantus vivit lege Romana! - Kubiak, Przemysław; Kulawiak-Cyrankowska, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
In the 14th-century treatise Ars cantus mensurabilis mensurata per modos iuris, the principles of menstrual music are explained by references to ius commune. This article aims to trace their Roman roots and to show that music too is sometimes governed by Roman law.